Gum Arabic Edible Coating Reduces Postharvest Decay and Alleviates Nutritional Quality Deterioration of Ponkan Fruit During Cold Storage - Huang, Qiang; Wan, Chunpeng; Zhang, Yajie; Chen, Chuying; Chen, Jinyin (Frontiers in Nutrition, 2021)
The storability recession during storage limits the postharvest storage life of Ponkan (Citrus reticulata Blanco cv. Ponkan) fruit and its nutritional value, which potentially lead to huge losses. To develop an effective technique to reduce Ponkan fruit postharvest decay and to maintain the nutritional quality, the preservation effect of 9, 12, and 15% postharvest gum arabic (GA) coatings on Ponkan fruit was investigated. The 12 and 15% GA coatings effectively reduced fruit decay as well as weight loss, retained higher total soluble solids (TSS) content, suppressed titratable acidity (TA) degradation, and postponed the rise in ripening index (RI). Moreover, the 12% GA-coated fruit exhibited a lower respiration rate, electrical conductivity, and malondialdehyde (MDA) accumulation than the uncoated (control) fruit. The 12% GA coating treatment decreased the loss of ascorbic acid (AsA), total phenols, and total flavonoids and maintained higher amounts of non-enzymatic antioxidants. Furthermore, the 12% GA coating treatment increased antioxidant enzymes' activities as well as delayed the reduction of total antioxidant capacity (TAC). These results suggest that, with the cold storage increasing time, the 12% GA-coated fruit exhibited better postharvest storability and higher nutritional quality than the control fruit. The GA coating treatment could be used as a commercial wax to improve postharvest storability, extend its storage life, and maintain the nutritional value of Ponkan fruit up to 120 days of cold storage.